Job satisfaction level of non-government Islamic religious school teachers - Ilhaamie Abdul Ghani Azmi,; Nor Raudah Siren, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Job satisfaction is a factor that influences ones intention to leave an organization. Sekolah Menengah Agama Rakyat (SMAR) is a religous school that is organized by the public. Thus, it lacks many facilities as well as face mismanagement. Hence, the purpose of this study was to assess the level of work satisfaction of religious teachers of SMAR in Malaysia based on the notions of work, relationship with colleagues, work environment, administration, level of income, promotion, welfare, recognition, workload and supervisory leadership by age, gender, marital status, education level, length of service, teaching, and income. The respondents were 278 SMAR teachers in Malaysia. Teacher Job Satisfaction Questionnaire (TJSQ) was used as an instrument. It consists of 71 items covering nine sub-scales, namely (a) present work, (b) relationship with colleagues, (c) work environment, (d) policies and administration, (e) income, (f) welfare, (g) recognition, (h) workload, and (i) supervision. Methods of t-test and ANOVA were used to analyze the data. The study found that there are significant differences on job satisfaction based on length of service and income level. The overall job satisfaction of these SMAR teachers is good. SMAR is an important institution in the development of human capital. The involvement and seriousness of SMAR teachers in the primer education system despite the fact that all the shortcomings demonstrate the sincerity and clear direction to guide and educate SMAR students to succeed in this world and hereafter.